Severe Cytomegalovirus pneumonia in a child with ectodermal dysplasia. - El haddar, Z.; El ouali, A.; Ghanam, A.; Babakhouya, A.; Rkain, M.; Benajiba, N. (European Journal of Pediatric Dermatology, 2024)
We report the case of a 3-month-old baby diagnosed with hypohidrotic ectodermal dysplasia and possible immunodeficiency, who died due to severe Cytomegalovirus pneumonia despite oxygen therapy and intravenous ganciclovir. The diagnosis of etodermal dysplasia was based on facial dysmorphism, hypohidrosis and hypotrichosis. Children with hypohidrotic ectodermal dysplasia are at risk for malignant hyperthermia, recurrent infections, and immunodeficiency, which can be severe and life-threatening.